"Healthy" food and the production of differentiated bodies in "anti-obesity" discourses and practices. Issue 1 (2nd January 2023) - Durocher, Myriam
ABSTRACT: In this article, I analyze various discourses held by governmental and health authorities, nutrition experts, and civil society organizations that advocate for the importance of consuming and having access to "healthy" food in order to prevent health-related risks associated with diet, such as the development of chronic diseases or conditions like "obesity." While "anti-obesity" discourses and practices aiming to "help" the population in the fight against "obesity" connect the issue to social or even food justice considerations, I discuss how the discourse of "healthy" food plays a key role both in problematizing the fat body and in the solutions brought forward to "fix it" as well as the broader "obesity" epidemic. I argue that these two roles are closely linked together – because "healthy" food is positioned as a solution to "obesity, " it reinforces the idea that fatness can be "acted on" or solved, and thus that it should be. I mobilize works emerging in critical food and fat studies to address how these discourses and practices contribute to further marginalizing those whose bodies do not match dominant ideas of health while creating harmful and discriminatory processes that have material and health-related consequences. I contend that scholars should be attentive to the broad effectivities of "healthy" food as arising from "anti-obesity, " or pro-health, discourses and practices as they contribute to further reproducing social injustices and can potentially materialize in damaging ways in individuals' bodies and health.